STANDARISASI KODE ETIK PROFESI BIMBINGAN DAN KONSELING - Bunyamin Bunyamin (Jurnal Sains Riset, 2022)
Counseling is a process of assistance carried out by professionals to individuals and groups of people to develop KES and handle KES-T. To become an expert in their field of counseling, they must be professional in their field of knowledge. Profession is something that must be accompanied by expertise and ethics. Even though there are rules that regulate the code of professional ethics, as we can see today, there are still many violations or misuse of the profession. The purpose of this study is that readers can understand the definition and function of the code of ethics, know the code of ethics in counseling, laws and regulations related to the counseling profession, know cases that can violate the code of ethics, and understand the skills of ethical behavior of a counseling teacher. Counselor qualifications in values, attitudes, skills, knowledge and insight, Storage and Use of Information., Relationships with Service Delivery, Relationships with Clients, Consultation with Peers, Transfer of CasesKeywords : standardization, professional code of ethics and guidance and counseling